The Influence of Think Pair Share on Self-Efficacy and Oral English Commitment in the Grow Bareng Community - Raharja, I Made Samuel; Wahyuningsih, M B Rini (Universitas Trunojoyo Madura, 2024)
English is very important as it is used globally for communication and opens up career opportunities. In the Grow Bareng Community, speaking in English is still low, so the